Foreign Stories and National Narratives: Yiddish and Fictionality in Jurek Becker’s Jakob the Liar and Edgar Hilsenrath’s The Nazi and the Barber - Emma Woelk (Humanities, 2019)
This article uses two examples of postwar German Jewish literature to explore the way in which these literary reflections on fictionality can also serve to subvert and complicate the national narratives that were developed in East and West Germany. The novels explored here, Jurek Becker’s Jakob the Liar (1969) and Edgar Hilsenrath’s The Nazi and the Barber (1977), directly thematize storytelling and specifically, storytelling in the context of the Holocaust and its aftermath. Both also share an interest in the intersections between German and Yiddish narrative traditions and reflect on the ways in which the latter was coopted by the former in the decades following the Second World War. Ultimately, this article argues that these two novels of lying create spaces in which the foundational myths of both German states are called into question.